Recent Advances in the Development of Materials for Terahertz Metamaterial Sensing. Issue 1 (17th October 2021) - Shen, Suling; Liu, Xudong; Shen, Yaochun; Qu, Junle; Pickwell‐MacPherson, Emma; Wei, Xunbin; Sun, Yiwen
Abstract: Terahertz metamaterial sensing (TMS) is a new interdisciplinary technology. A TMS system employs terahertz waves as the pumping source, these then interact with the sample and carry the substance information, e.g., refractive index, absorption spectra. These properties are relevant to the molecular rotation and vibration states produced by a surface‐plasmon‐polariton‐like effect. TMS technology is usually characterized by large penetration depth and high sensitivity. Owing to these advantages, TMS may be used for ultratrace detection and consequently has a wide range of practical applications in biomedicine, food safety, environmental monitoring, industry and agriculture, material characterization, and safety inspection. Furthermore, TMS performance is determined not only by the structural topology of metamaterials, but also by their compositions and substrates. This paper reviews the essential fundamentals, relevant applications, and recent advances in TMS technology with a focus on the influence of material selection on TMS performance. This review is envisaged to be used as a key reference for developing TMS‐based functional devices with enhanced characteristics. Abstract : Terahertz metamaterial sensing (TMS) may be used for ultratrace detection, implying a wide range of applications. This paper reviews essential fundamentals, relevant applications, and recent advances in TMS technology with a focus on the influence of material selection on TMS performance. This review is envisaged to be used as a key reference for developing TMS‐based functional devices with enhanced characteristics.